1992
DOI: 10.1007/bf01308184
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of antithrombin III in acute experimental pancreatitis in rats

Abstract: In the present study we investigated the therapeutic action of antithrombin III (AT III) in taurocholate-induced experimental pancreatitis with high lethality in rats. High-dose AT III treatment greatly improved the survival rate not only when given as pretreatment but also when given 2 hr after induction. No favorable effect on survival rate was observed on administration after 5 hr. Both intravascular and intraperitoneal AT III administration locally restored decreased AT III levels in the peritoneal cavity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 18 publications
0
18
0
4
Order By: Relevance
“…In taurocholate-induced experimental pancreatitis in rats, high dose AT treatment was shown to improve survival (Bleeker et al, 1992). In cerulein-induced AP, AT supplementation inhibited the release of high mobility group box 1 protein (HMGB1) as well as other proinflammatory cytokines in rats (Hagiwara et al, 2009).…”
Section: Antithrombin In Apmentioning
confidence: 99%
“…In taurocholate-induced experimental pancreatitis in rats, high dose AT treatment was shown to improve survival (Bleeker et al, 1992). In cerulein-induced AP, AT supplementation inhibited the release of high mobility group box 1 protein (HMGB1) as well as other proinflammatory cytokines in rats (Hagiwara et al, 2009).…”
Section: Antithrombin In Apmentioning
confidence: 99%
“…Several recent animal experiments, using 1&15 times the pretreatment high dose of antithrombin I11 alone (100-250 unitskg), have shown beneficial prophylactic effects on mortality and restoration of coagulation abnormalities resulting from DIC and/or MSOF [7,8]. The mechanisms of the beneficial effects on DIC are unknown.…”
Section: Discussionmentioning
confidence: 95%
“…The timing of onset of antithrombin I11 administration could be a pivotal factor; we started infusion as soon as the diagnosis of DIC was established, because high-dose antithrombin I11 treatment had shown only prophylactic effects in animal experiments [7,8]. The per-day dosages of antithrombin I11 concentrates were 3-6 times the usual, and were continued for 2 or 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…In the later study, a LMWH (Certoparin) was used but offered no benefit compared with placebo based on the frequency and severity of acute post-ERCP pancreatitis. The authors speculated that the discrepancy between the results of this clinical trial and the experimentally proven effects of heparin [20][21][22][23][24][25][26][27][28] might be explained by the drug chosen for the study. It is possible that the antiinflammatory capability of the heparin molecule is destroyed during the fragmentation process.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin inhibits pancreatic proteases in both plasma and pancreatic tissue in animal models of acute pancreatitis, improves pancreatic microcirculation, and inhibits inflammatory cascade [20][21][22][23][24][25][26][27][28]. Salas et al [25] reported that heparin inhibits tumor necrosis factor (TNF)-induced interactions of leukocytes and endothelium, thereby reducing inflammation.…”
mentioning
confidence: 99%